A Study of Advanced Online Shopping Web Application with its Impact on Consumer Intention to Purchase Online and Seller Intention to Sell Online - Wellappili, Ishan Kalpadith; Samarasinghe, Jayani Chamika; D.H, Mishara Samadhi; Weerasinghe, Nimrekha Thathyani; De silva, Dilshan; Samarasekara, Piyumika (International Journal of Engineering and Management Research, 2022)
The purpose of this study is to develop an advanced web application for online shopping and to increase the customer and seller intention to buy and sell via online web platform. This study is focused on variables of website characteristics, customer and seller interactions, physical telepresence and consumers thoughts and their feedback towards online shopping web applications. And behavioral controls of customers and sellers which will describe the consumer thoughts and intention towards the online purchasing. This study reveals the customer’s and seller’s perspective and attitude towards the online purchasing and online shopping. And this study explores about factors that affect to build a trust and intention in consumers towards online purchasing. A web application will be developed by considering above mentioned factors. Smart bay is the improved web application that is planning to develop by analyzing above mentioned all focused areas to perform with vast area of functions in very user-friendly environment.